Lyme Meningitis Characteristics cf Viral Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The clinical and laboratory findings in 12 patients (ages 3-18 yrs) with Lyme meningitis (LM) were compared with 10 (ages 2-15) diagnosed with viral meningitis (VM), in a retrospective analysis of records of children admitted to Alfred I duPont Hospital for Children, Wilmington, DE, between 1990 and 1996.